EVALUATION AND STRATEGY FOR DISTRIBUTION OF SUBSIDIZED FERTILIZER IN BIG ACEH DISTRICT - Afilia Ulfa; Lukman Hakim; Irfan Zikri (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
Subsidized fertilizer is fertilizer whose procurement and distribution receive subsidies from the Government for farmers' needs which is carried out on the basis of a Government program. Due to the government's limitations in providing fertilizer subsidies within the framework of government programs, subsidized fertilizer is only intended for agricultural businesses which include food crop farmers, livestock and community plantations. The implementation of the subsidized fertilizer policy is still experiencing obstacles such as various kinds of problems. So the implementation of the policy will not run optimally. This problem will have an impact on society, especially farmers, so that farmers will not get their rights regarding subsidized fertilizer. Problems that arise include a shortage of urea fertilizer at the farmer level due to the hoarding of subsidized urea fertilizer carried out by irresponsible individuals. Determination of the sample using the Cluster Sampling technique with the Two-Stage Cluster Sampling method. The method used is effectiveness analysis,Importance Performance Analysis (IPA) and AnalysisQSPM. The results of this research show that the level of effectiveness of the fertilizer subsidy policy for farmers in Aceh Besar Regency based on six overall success indicators can be categorized as quite effective with an effectiveness value of 69.45% and the evaluation. The strategy for distributing subsidized fertilizer in Aceh Besar Regency is 1) Optimal supervision in the form of a complaint service; 2) Installation of HET price banners and sanctions; 3) Assistance to a team of experts in preparing the RDKK for the redemption process; and 4) Supervision of retail kiosk stock warehouses.